Pengaruh Pengungkapan ESG, Profitability, dan IOS Terhadap Nilai Perusahaan pada Perusahaan Pertambangan di BEI 2022-2024 - Pratiwi, Anggun; Sandari, Tries Ellia (Jurnal Riset Manajemen dan Akuntansi, 2026)
This research uses a quantitative descriptive approach to analyze how ESG Disclosure, Profitability, and Investment Opportunity Set (IOS) influence Firm Value. The study focuses on 11 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Data was collected and analyzed using purposive sampling and multiple linear regression with SPSS 26. The partial results (t-tests) indicate that ESG Disclosure and Profitability do not have a significant individual impact on Firm Value. However, IOS was found to have a positive and significant effect. A simultaneous test (F-test) shows that, collectively, ESG Disclosure, Profitability, and IOS significantly affect Firm Value.